The impact of occurrence of tinnitus in first degree relatives on the severity of disease among subjects - T. J., Mosanya; T., Yusuf; A., Daniel; O. A., Ogundoyin; P. A., Onakoya; A. A., Adeosun; K. G., AbdulWasiu-Idowu; B. O., Yusuf; J. O., Adeolu; W. A., Adedeji; I., Musa; J. O., Ijitola; et al. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Background: The aetiology of tinnitus and the factors that contribute to the exacerbation from mild to severe tinnitus are poorly known. Particularly, a role of genetics has been proposed for tinnitus, although this has not been conclusive. In order to establish a possible role for heritability in our population, we explored the history of tinnitus among first degree family members of those suffering from tinnitus using cross-sectional community-based strategy. Methods: There were 300 subjects with idiopathic tinnitus with mean (±SD) age of 51.88 (±15.11, range=19-80 years) comprising 169 males and 131 females. Results: Tinnitus was severe in 37.9% and bilateral in 65.1% while 26.6% reported having family members with history of tinnitus. TInnitus was significantly more severe (p<0.001) and more frequent (p<0.001); and the psychological distress related to tinnitus (p<0.001) measured by the mini-TQ was worse among those with family history compared to those without. Bivariate analysis reveals that the presence of tinnitus in other family members, occurrence of tinnitus for more than 3 months (p=0.003), increasing age (0.001) and higher mean mini-TQ scores (0.001) showed significant association with severity of tinnitus. Logistic regression reveals that presence of tinnitus in other family members increases the odds of frequency of tinnitus by 5.08 (95% CI=1.70-15.12), elevates the mean scores of the mini-TQ by 1.31 (95% CI=1.20-1.44) while increasing age greater than 50 years increases the odds of severity of disease by 2.81 (95%CI=1.59-4.94). Conclusions: We conclude that the findings of significant correlation between presence of tinnitus in first degree relatives and severity of tinnitus among the subjects provides an empirical evidence to explore a possible genetic aetiology for severe tinnitus in our population.